Mercator e sua contribuição à cartografia e ao estudo dos mapas - Gurgel, Abilio Castro (2012)
The primary source of this research is Gerardus Mercator, born in 1512 on Rupelmond Villa, Flanders area, now Belgium, and deceased in Duisburg, on Cleves dukedom, current in western Germany, in 1594. Mercator, besides a cartographer, was calligrapher, carver and engraver in copper plates (used for graphic printing), manufacturer of scientific instruments (compasses, rulers and squares), of terrestrial and celestial globes and, also, map editor. However, is the world map of 1569, in a map projection became different from everything that had in the moment and remained for more than 400 years as standard maps that will be in this Gerardus Mercator s universe the central focus of this work. The chapter 1 of the research contains a brief explanation about the origin of maps and the explanation of geography in antiquity Greek to may understand the basis on which the renaissance cartographers, including Mercator, could resume studies of maps and cartographic projections. The chapter 2 studies Mercator and his social, political and economical contexts, besides the specific Flanders politic, the religious question with the rise of Protestant Reformation and how all this situation was connected with the life trajectory of the cartographer. The chapter 3 will analyze specifically his most famous map of 1569, its finality, purposes, consequences and how it was elaborated. It will be shown what were the differential in relation to other maps made at the time and, mainly, how the Ptolemaic maps was resumed by Mercator